Rock art at the pleistocene/holocene boundary in Eastern South America. - Walter A Neves (Public Library of Science (PLoS), 2012)
Background Most investigations regarding the first americans have primarily focused on four themes: when the New World was settled by humans; where they came from; how many migrations or colonization pulses from elsewhere were involved in the process; and what kinds of subsistence patterns and material culture they developed during the first millennia of colonization. Little is known, however, about the symbolic world of the first humans who settled the New World, because artistic manifestations either as rock-art, ornaments, and portable art objects dated to the Pleistocene/Holocene transition are exceedingly rare in the Americas. Methodology/principal findings Here we report a pecked anthropomorphic figure engraved in the bedrock of Lapa do Santo, an archaeological site located in Central Brazil. The horizontal projection of the radiocarbon ages obtained at the north profile suggests a minimum age of 9,370 ± 40 BP, (cal BP 10,700 to 10,500) for the petroglyph that is further supported by optically stimulated luminescence (OSL) dates from sediment in the same stratigraphic unit, located between two ages from 11.7 ± 0.8 ka BP to 9.9 ± 0.7 ka BP. Conclusions These data allow us to suggest that the anthropomorphic figure is the oldest reliably dated figurative petroglyph ever found in the New World, indicating that cultural variability during the Pleistocene/Holocene boundary in South America was not restricted to stone tools and subsistence, but also encompassed the symbolic dimension.